MFCC based recognition of repetitions and prolongations in stuttered speech using k-NN and LDA - Lim, Sin Chee; Ooi, Chia Ai; Hariharan, Muthusamy; Sazali, Yaacob, Prof. (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/